Field Application and Validation of a Seismic Bedload Transport Model. Issue 5 (10th May 2020) - Bakker, Maarten; Gimbert, Florent; Geay, Thomas; Misset, Clément; Zanker, Sébastien; Recking, Alain
Abstract: Bedload transport drives morphological changes in gravel‐bed streams and sediment transfer in catchments. The large impact forces associated with bedload motion and its highly dynamic spatiotemporal nature make it difficult to monitor bedload transport in the field. In this study, we revise a physically‐based model of bedload‐induced seismic ground motion proposed by Tsai et al. (2012) and apply it to invert bedload flux from seismic measurements alongside an Alpine stream. First, we constrain the seismic response of a braided river reach with a simple active experiment using a series of large‐rock impacts. This allows the characterization of surface wave propagation and attenuation with distance from the impact source. Second, we distinguish bedload‐generated ground vibrations from those caused by turbulent flow using frequency‐based scaling relationships between seismic power and discharge. Finally, absolute bedload transport rates are quantified from seismic measurements using inverse modeling based on a simplified formulation of bedload particle motion. The results are verified with a large data set of bedload samples (between 0.01 and 1 kg/m/s), demonstrating that seismic measurements can provide an indirect measure for bedload flux with an uncertainty of less than one order of magnitude. Larger deviations may be due to the contribution of turbulent flow effects and remaining uncertainties in particle impact mechanics (elasticity and velocity). When constraining these uncertainties, seismic monitoring may provide an accurate and continuous means to investigate bedload dynamics in gravel‐bed streams. Key Points: Bedload fluxes are derived independently from bank‐side seismic measurements with an uncertainty of less than one order of magnitude Simple experiments with large‐rock impacts are used to calibrate seismic response and constrain inverted bedload rates Scaling seismic power with discharge allows bedload‐generated vibrations to be isolated and gives insight into bedload temporal dynamics